A simulation-based study of arrival-departure flow management - Neo, Eugene Rui Ming (2016)
Over the past decades, there has been a significant growth in aviation traffic, especially across Asia. This is mainly caused by the introduction of many budget airlines, which greatly reduces the flight tickets, making travelling less expensive. This trend has raised the need for airports to be bigger and their facilities to be more efficient. However, some countries have failed to manage this issue, resulting in delays and slot limitations. Most major capital city airport in Southeast Asia has issues with congestion. Singapore’s Changi International Airport, is an example.